2015
DOI: 10.1128/iai.02463-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dendritic Cells in the Pathogenesis of Whipple's Disease

Abstract: c Accumulation of Tropheryma whipplei-stuffed macrophages in the duodenum, impaired T. whipplei-specific Th1 responses, and weak secretion of interleukin-12 (IL-12) are hallmarks of classical Whipple's disease (CWD). This study addresses dendritic cell (DC) functionality during CWD. We documented composition, distribution, and functionality of DC ex vivo or after in vitro maturation by fluorescence-activated cell sorting (FACS) and by immunohistochemistry in situ. A decrease in peripheral DC of untreated CWD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The bacterium is internalized by mucosal macrophages which then migrate to the deeper mucosa but seem unable to successfully kill the bacteria. This is due in part to a bacterium-induced decreased expression of CD11b by these macrophages leading to inappropriate antigen presentation by the macrophages and the dendritic cells (77,79). This results in an immunological environment with increased expression of IL-10, CCL-18 (CC chemokine ligand 18), and TGF-␤ and low expression of IL-12 and IFN-␥ (47,59,61,75,77,(80)(81)(82).…”
Section: Pathogenesis Predisposing Factors For Classic Whipple's Diseasementioning
confidence: 99%
“…The bacterium is internalized by mucosal macrophages which then migrate to the deeper mucosa but seem unable to successfully kill the bacteria. This is due in part to a bacterium-induced decreased expression of CD11b by these macrophages leading to inappropriate antigen presentation by the macrophages and the dendritic cells (77,79). This results in an immunological environment with increased expression of IL-10, CCL-18 (CC chemokine ligand 18), and TGF-␤ and low expression of IL-12 and IFN-␥ (47,59,61,75,77,(80)(81)(82).…”
Section: Pathogenesis Predisposing Factors For Classic Whipple's Diseasementioning
confidence: 99%
“…Several research findings support an immunogenetic predisposition to full-fledged manifestation of WD: namely, colonization by T. whipplei does not lead to disease in all individuals, 4,18 specific HLA alleles and cytokine gene polymorphisms predispose some individuals to WD development, 24,25 and that patients with WD have reduced titers of antibodies compared to healthy, colonized individuals in addition to other cellular immune dysregulation. 4,9,18,[26][27][28] The heterogeneous and complex interactions of T. whipplei with the human immune system is beyond the reach of our current understanding, but may account for the diversity of disease presentation. This case report highlights the challenge of diagnosing a rare disease with an atypical clinical presentation, but may help serve as a reminder to consider unusual infections in patients with a similar constellation of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In addition, flow cytometry and functional assays demonstrated that inflammatory reactions against T. whipplei are prevented by impaired maturation and IL-12 production of dendritic cells, an increased frequency and activation of functionally active regulatory T cells, a higher sensitivity of T cells to regulation, a predominance of Th2 activity accompanied by a reduced unspecific T-helper-1 reactivity, and, most importantly, the absence of T. whipplei-specific T-cell reactions in the blood and duodenal lamina propria. [2][3][4][5][6]9 These cellular deficiencies are reflected by low serum concentrations of IgG 2 and of T. whipplei-specific immunoglobulins in CWD patients and reduced duodenal secretion of IgA and IgG 2 with only low amounts of T. whipplei-specific IgA, [6][7][8] The predominance of tolerogenic reactions was interpreted as a permissive factor allowing for the persistence and spread of T. whipplei. 1,5,9,11 In this context, symptoms and signs of systemic inflammation such as fever, elevated blood sedimentation rate, and C-reactive protein were difficult to explain because the evidence outlined above and the usual absence of T. whipplei from the blood clearly argues against a pathogen-directed immune response as their cause.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inflammatory reactions within the intestinal mucosa of CWD patients are dominated by regulatory rather than pathogen-directed immune mechanisms. [2][3][4][5][6][7][8][9] On the other hand, CWD is characterized by systemic inflammation as reflected by elevated C-reactive protein, increased erythrocyte sedimentation rate, and leukocytosis. 1,10 Although the tolerogenic mucosal immune reaction was attributed to a subtle immune defect of the host and to antiinflammatory effects of T. whipplei, 1,11 little is known about the causes of the systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%